2003
DOI: 10.1159/000074288
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Hepatitis B Virus 2 Months Prior to Hepatitis Surface Antigen Positivity of Donor Blood

Abstract: An hepatitis surface antigen(HBsAg)-negative donation transmitted hepatitis B virus (HBV) of the very common genotype A/HBsAg subtype adw2 to the recipient of the erythrocyte concentrate. Two months later the donor became borderline HBsAg-positive. The infectious donation was tested retrospectively by real time PCR and contained approximately 2,000 viral genomes/ml, an amount which would have been well detectable by minipool nucleic acid amplification test (NAT) for HBV DNA at the usual detection limit of 1,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…There also have been well‐documented cases of donors testing confirmed HBsAg‐positive after hepatitis B vaccination, which has led to policies to defer donors for 3‐4 weeks after vaccination 21‐25 . Finally, it must be appreciated that HBsAg will not be detectable at the beginning and end of the disease process even though infectious HBV DNA may be present 26‐28 …”
Section: Current Molecular Biology Of Hbv and Diagnostic Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…There also have been well‐documented cases of donors testing confirmed HBsAg‐positive after hepatitis B vaccination, which has led to policies to defer donors for 3‐4 weeks after vaccination 21‐25 . Finally, it must be appreciated that HBsAg will not be detectable at the beginning and end of the disease process even though infectious HBV DNA may be present 26‐28 …”
Section: Current Molecular Biology Of Hbv and Diagnostic Methodologymentioning
confidence: 99%
“…[21][22][23][24][25] Finally, it must be appreciated that HBsAg will not be detectable at the beginning and end of the disease process even though infectious HBV DNA may be present. [26][27][28]…”
Section: Hbsag Measurementmentioning
confidence: 99%
“…org.uk) and many European countries are now also screened for HCV RNA by nucleic acid amplification technology (NAT). Similarly, HBV may be transmitted through blood donation in the absence of HBsAg (Meisel et al 2003) The post mortem degradation of the viral genome and production of 'inhibitors' which interfere with the detection of viral nucleic acid, and presence of bacterial DNase and RNase may be dependent on the time of sampling after death (Stanworth et al 2000). Previous studies have indicated that when samples from known AIDS patients taken before and after death were tested by PCR for HIV, specificity was high but sensitivity low (Burtonboye and Delloye 1996).…”
Section: Introductionmentioning
confidence: 99%
“…HBV ist, solange HBeAg vorliegt und keine Therapie erfolgt, genetisch sehr stabil, sodass schon kleine Sequenzunterschiede gegen einen Zusammenhang sprechen.Aufgrund dieser ausgeprägten Stabilität liegt bei einem Großteil der deutschen HBV-Träger eine völlig identische S-Gen-Sequenz des Genotyps A vor ( [13,14] und nicht publizierte eigene Ergebnisse). Bei 3 nosokomialen Über-tragungen dieser HBV-Variante war daher die Zusammenhangsfrage nur durch Verlaufsbeobachtungen und Anti-HBcSerokonversionen bzw.…”
Section: Erkennung Von Hbv-übertragungenunclassified
“…IgM-Anti-HBcMessungen eruierbar. Es handelte sich um 6 Patienten, die von einem Herzchirurgen infiziert wurden [13], um eine Blutempfängerin [14] und um einen HBV-Ausbruch bei 15 Heimbewohnern durch Hygienefehler bei Blutentnahmen bzw. Injektionen (M. Monazahian, W. Gerlich, nicht publiziert).…”
Section: Erkennung Von Hbv-übertragungenunclassified